The Potential of Indonesian Zakat for Zakatnomics Improvement - Taxonomic Analysis Techniques - Zulfikar Hasan (International Journal of Zakat, 2022)
Research made by researchers is related to zakat which can improve the economy of the ummah. Through zakatnomics how to raise awareness to build a new economic order to achieve happiness, life balance, and human dignity which is based on the spirit and noble values ​​of the zakat law. Namely the spirit of devotion, the spirit of productivity, and a fair economy, and the spirit of grounding ZISWAF in the practice of life. Research made by researchers uses qualitative methods with Taxonomic Analysis Techniques, where researchers generally look at the problems faced by Baznas RI to optimize the potential of zakat which will have a good impact on the ummah. The results of this study show that the potential for zakat in Indonesia is very large, in 2020 the potential for zakat in Indonesia will reach 230 trillion rupiahs, but the absorption of zakat funds is still below 10 percent. Because there are several obstacles faced by BAZNAS to increase the existing potential. Hopefully, this research will give a little contribution to the academic world and practitioners, and there will continue to be research related to zakat in Indonesia.